Influence of ethrel on ripening and quality of persimmon (Diospyros kaki) - BAKSHI, PARSHANT; KUMAR, RAKESH; WALI, V K; BHUSHAN, BHARAT (The Indian Journal of Agricultural Sciences, 2015)
The present investigation was conducted to study the effect of post-harvest ethrel treatment on ripening and quality of persimmon (Diospyros kaki Thunb.) under ambient (24 Â± 2Â°C) as well as refrigerated (3-6°C) conditions. Fully matured persimmon cv. Hachiya fruits were dipped in ethrel solution of varying concentrations (50, 100, 150 and 200 ppm) or with control (water dip). The observations on per cent physiological loss in weight (PLW), per cent ripening and spoilage, fruit length (cm) and breadth (cm), and quality parameters, viz. total soluble solids (°B), titratable acidity (%), total sugars (%), reducing sugars (%) and TSS: acid content were recorded at regular interval till the fruits were acceptable. Results of the study revealed that PLW (%) increased with the increase in storage period under both the storage conditions. All the quality parameters, like TSS, total sugars, reducing sugars and TSS: acid ratio were influenced by ethrel treatment but the acidity remains unaffected. The fruits treated with higher concentration of ethrel (150 or 200 ppm) showed more ethylene injury (spots on fruits), while those treated with lower concentration (50 or 100 ppm) or untreated did not show any such injury when stored under refrigerated condition. A dip in 100 ppm ethrel for 1 minute was found to be the best for persimmon cv. Hachiya under both the storage conditions.